2018
DOI: 10.4236/ojgen.2018.82002
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Abnormalities in 238 Couples with Recurrent Miscarriages in Morocco

Abstract: Purpose: A proportion of cases with repeated abortion are caused by chromosomal abnormality in one of the parents. The purpose of this study was to assess the frequency and nature of chromosomal aberrations that contribute to the occurrence of recurrent miscarriages. Several studies have been done to determine the role of chromosomal abnormalities in couples with recurrent spontaneous abortion in various countries. None of these studies was done in Morocco. Material and Methods: Cytogenetic study was done for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
(29 reference statements)
1
6
1
Order By: Relevance
“…The incidence of chromosomal abnormalities was higher among females (7.14%) compared to males (5.35%); some studies reported such difference to be statistically significant[ 25 29 ] whereas others, including the current study, did not find the difference to be of statistical significance ( P = 0.435). [ 30 31 ] This higher female frequency may be explained by the fact that chromosomal anomalies compatible with fertility in females may be combined with sterility in males.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…The incidence of chromosomal abnormalities was higher among females (7.14%) compared to males (5.35%); some studies reported such difference to be statistically significant[ 25 29 ] whereas others, including the current study, did not find the difference to be of statistical significance ( P = 0.435). [ 30 31 ] This higher female frequency may be explained by the fact that chromosomal anomalies compatible with fertility in females may be combined with sterility in males.…”
Section: Discussioncontrasting
confidence: 66%
“…[ 28 34 ] Reciprocal translocations were the most commonly identified balanced chromosomal aberrations in couples with RPL, in accord with previous studies. [ 20 23 25 29 ] If one partner of a couple carries a balanced chromosomal translocation, the probability of miscarriage is nearly doubled. [ 38 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases, this cytogenetic study of the abortion product and the karyotype of the parents is necessary if we want to prevent the CHF repeatedly by proposing genetic counseling to infertile couples. 2,9 The absence of histological abnormality in our study accounts for nearly 40% of the cases. Infectious causes such as malaria must be mentioned in the context of fever in the first trimester of pregnancy in tropical environments.…”
Section: Pathological Anatomymentioning
confidence: 49%
“…The first-quarter miscarriage is one of the main reasons for consultation with gynecological emergencies, since it complicates 10 to 25% of pregnancies and will affect about 25% of women during their genital life. 1,2 In spite of this frequency, doctors as well as patients often do not attach great importance to it, which is why there is little study devoted to it. 3 The question that any doctor should ask when faced with a first miscarriage is this an ordinary accident in the woman's obstetric life or the beginning of a series of spontaneous abortions to come?…”
Section: Introductionmentioning
confidence: 99%